ASSIMILATION IDENTITY OF THE SAORAJA LAPINCENG TRADITIONAL HOUSE, BALUSU, INDONESIA - Hendra, Hendra (Universitas Negeri Makassar, 2022)
This research was carried out with the aim of finding out: 1) To find out the description of the community's cultural system regarding the concept of Islamic architecture found in the Saoraja traditional house in Balusu Village, Balusu sub-district, Barru Regency. 2) To find out the values contained in the Islamic architectural concept in the Saoraja Lapinceng traditional house in Balusu Village, Balusu District, Barru Regency. 3) To find out the community's strategy in maintaining the concept of Islamic architecture in the Saoraja Lapinceng Traditional house in Balusu Village, Balusu District, Barru Regency. The results of the research show that: 1) The description of the community's cultural system regarding the concept of Islamic architecture found in the Saoraja Lapinceng traditional house in Balusu Village, Balusu District, Barru Regency is that it has several cultural systems, namely indigenous ethnic groups, major religious cultural systems, cultural systems Indonesia, and foreign cultural systems. 2) The application of Islamic values contained in the concept of Islamic architecture in the Saoraja Lapinceng traditional house in Balusu Village, Balusu District, Barru Regency is that there are several values contained, namely Habluminallah values, Habluminannas values, and Habluminal'alam values. 3) The community's strategy in maintaining the Islamic architectural concept in the Saoraja Lapinceng traditional house in Balusu Village, Balusu District, Barru Regency is to use adaptive reuse, which is one way to conserve historic buildings by transferring old functions to new functions.